International Financial Reporting Standards (IFRS) and income smoothing activities of banks: Evidence from Australia and New Zealand commercial banks - Abdul Adzis, Azira; Tripe, David W.L.; Dunmore, Paul V. (Social Science Electronic Publishing, Inc, 2010)
This study investigates the impact of IFRS on income smoothing activities through loan loss provisions for Australia and New Zealand banks over the period 1995-2009. Prior to IFRS implementation, bank loans provisioning is subject to managerial manipulation, possibly due to the weakness in GAAP that provides room for managers to manage earnings.We conjecture that the robust disclosure requirements under IFRS (particularly IAS 39) could mitigate income smoothing activities of the IFRS adopters.Our paper examines the effects of IFRS adoption on Australia and New Zealand banks as previous studies give much attention to the European Union (EU) samples.The findings demonstrate that income smoothing activities of banks in Australia and New Zealand are reduced after IFRS adoption.